PENINGKATAN KETERAMPILAN SOSIAL MELALUI BERMAIN ANGIN PUYUH (Penelitian Tindakan pada Kelas B TK Mujahidin, Kelurahan Kedoya, Kebon Jeruk, Jakarta Barat Tahun 2015) - Khairul Huda (Jurnal Ilmiah Mandala Education (JIME), 2016)
The aims of this research is to get information and data about the effort to increase children’s social skill in grade B kindergarten through playing of angin puyuh in TK Mujahidin, Kedoya Selatan, Jakarta Barat.Research method used action research method. This method conduced in two cycles according to Kemmis and Taggart model which consist of 4 stages (plan, action, observation, and reflection). Data collecting techniques used field notes, interview, documentation, and observation. Sample was taken from 18 children of 5-6 years old.The result of the research shows that children’s skill through playing of angin puyuh could increase of grade B kindergarten. Analysis of data obtained from the comparison between pre-action, and cycles two score. The end result of overall analysis of data is the percentage increase of 49.3% which showed from pre-action the class average is 34.7 up to 84 at cycles two result.